Розповсюдження акустичних хвиль у кристалах вольфрамату кальцію - Buryi, O.A.; Vynnyk, D.M.; Voroniak, T.I.; Stasyshyn, I.V.; Ratych, A.T.; Andrushchak, A.S. (Publishing house "Academperiodika", 2023)
On the basis of the solution of Christoffel equation, the phase-velocity surfaces for a quasilongitudinal acoustic wave (AW) and the fast and slow quasi-transverse AWS in the CaWO4 crystals have been plotted, and the extreme velocity value for each AW type and the direction of its realization have been determined. It is shown that the maximum shear angle occurs for the AW propagating in the (001) plane; in the case, the shear angle can reach a value of about 45∘ for the quasi-transverse AW, and about 18∘ for the quasi-longitudinal one. The quadratic anisotropy coefficients W1 and W2 for various AW propagation directions are determined. It is shown that there exist such directions of the quasi-transverse AW propagation in the CaWO4 crystal for which the divergence (the quadratic anisotropy coefficient |W2|) significantly exceeds the divergence that would occur in the case of isotropic medium. A direction in which the crystal anisotropy induces an additional focusing of the acoustic beam of the slow quasitransverse AW or an additional divergence of the acoustic beam of the fast quasi-transverse AW is determined. The experimental values of the velocities and shear angles of the AWS are presented, which confirm the reliability of the obtained calculation results.